About the khans Giyath ad-Din ibn Tashtimur and Giyath ad-Din ibn Shadibek - Reva R.Yu. (Золотоордынское обозрение)
The purpose of this study, based on a comparison of written and numismatic sources, is to reconstruct facts from the life and reign of two different khans who bore the name Giyath al-Din. Reserch materials: The article uses both previously published materials from written sources and recently discovered numismatic data (some are published for the first time). Among the written sources, texts are drawn that do not directly contain the name Giyath al-Din, however, according to the author, they describe some moments in the life of characters with this name. Scientific novelty and research results: it was established that the proposed A.L. Ponomarev’s version of the origin of Khan Bek-Sufi was not confirmed. In the Genoese texts of Kaffa, the emperor, the brother of “Tavlatberdi”, should be considered Giyath al-Din, the son of Tashtimur. This khan ascended the throne in AH 819. He renounced power In the next decade, but remained to live in Crimea and retained his title. He was killed in AH 838. by order of Sayyid Ahmad II. He was the father of Hajji Giray khan. Another ruler was Giyath al-Din, son of Shadibek-khan. At the end of AH 828 – beginning 829 he seized the throne of Saray, restoring the power of the Numaghans in the Great Horde. Died in AH 831. His son Mustafa was the khan of the Great Horde for some time, then he was the ruler of Khorezm for several years.